THE STRATEGY FOR CREATION OF THE MODERN CONCEPT OF INTEGRATIVE-HOLISTIC EDUCATION (A CASE STUDY OF MINING SCHOOLS OF THE URALS) - N. K. Chapaev; M. A. Choshanov (Russian State Vocational Pedagogical University, 2017)
Introduction. The relevance of the problem under study is caused by the contradiction between the necessity of fundamentalization of education, raising it to the level of the requirements of integral human development and the deepening disintegration of all sides of his life, including vocational education.The aim of the present publication is philosophical and pedagogical reflection and development of mechanisms for mainstreaming integrative-holistic approach when building a hypothetical model of professional education, aimed at provision of strategic turn towards more balanced (dialectical) approach to the traditional values of education. In particular, it concerns the experience of mining schools of the Urals.Methods. A leading approach to the study of this problem is an integrativeholistic approach (PPI) that can identify the holistic nature of the pedagogical system in which: a) inter-transformation of cooperated parts occurs not at the expense of each other, but on behalf of each other part; b) the existence of common points of contact between the cooperated components is complemented by the coexistence of the opposite, sometimes mutually exclusive sides of life; c) the idea of the priority of the whole is in harmony with the idea of polycentrism.Results and scientific novelty. The study shows the failure of the monopoly of the prevailing doctrine of competence-based education as a means for the successful resolution of global problems of reintegration of human existence and therefore postulated the necessity of antinomization (diversification) of education. The authors make the original hypothesis of the construction of the concept of vocational education on the basis of the reconstruction of experience of the mining schools of the Urals and prove the prospectivity of integrative-holistic strategy of reconstruction of educational experience in modern conditions. The system of technological and methodological support of the process of reconstruction of educational experience in modern conditions on the basis of an integrative-holistic approach is developed and presented.Practical significance. The materials of this article can be useful when modeling, the design and construction of educational organizations (systems) that meet the needs of development, the formation and socialisation of a multidimensional personality and the requirements of emerging new communications reality in the relationship of education, production and social environment.